“The cross” against “the sword”. Russia, intellectuals and the national idea of 1914 - Marković, Saša S. (Sociološki pregled, 2017)
The history of the Great War 1914-1918, in focus in the years marking a hundred year anniversary, is more than ever enriched by researches which aim is not only to shade light on military-political events only. Increasingly, professional community, but also every interested citizen, are able to learn about various aspects of social ideas and the creation of national identity. Russian social thought during the XIX century had an exceptionally complex development. In search for a content of their own identity the Russians had been looking to the West hoping it will offer them something new, but had also tried to express own autochthonous slavophile profile through tradition. Undeniably huge Empire had allowed for highlighting a specific role Russia had in development of humanity. At the beginning of the XX century a Russian social thought which was guiding the state had tried to amalgamate Christian universalism with nationalist egoism. The result was exceptional emotionality of the national idea which relied on intuitivism, a specific Russian role and its messianism. Rationally set out treatment of the state interests, although present in the final consequence of the decision, was marked by compassion. The Russian Tzar Nicholas II, although the militarypolitical and economic situation in the country was not suggesting readiness, stood up in defence of the “Slavic brothers”. The Russian people had supported the sentiment, and the German imperialism counted on it because it was itself driven by the “Teutonic domination”.